2021
DOI: 10.3389/fpsyt.2021.695096
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Views With Regard to Personal Recovery in Forensic Psychiatry in German-Speaking Switzerland—An Explorative Study

Abstract: Recovery orientation (RO) is a modality of supporting patients to improve self-determination, leading a meaningful life and well-being in general. This approach is widely studied in general psychiatry, but evidence is lacking for forensic inpatient settings in Switzerland. While secure forensic clinics tend to be regarded as total institutions, which are an anathema to RO, a project to implement RO interventions in this setting was financed by the Swiss Federal Office of Justice. This explorative study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…This is consistent with the broader literature that indicates mental health staff generally tend to attribute patient aggression to internal factors, such as patient psychopathology, more readily than environmental or situational factors including communication between the patient, staff member, and other patients ( 92 ). A study found that staff reframe restrictive practise as acts of compassion and necessary means of managing risk, thereby reducing feelings of unease derived from constantly acting against the will and wishes of their patients ( 93 ).…”
Section: The Potential For Abuse Of Power—staff Attitudes and Accountabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…This is consistent with the broader literature that indicates mental health staff generally tend to attribute patient aggression to internal factors, such as patient psychopathology, more readily than environmental or situational factors including communication between the patient, staff member, and other patients ( 92 ). A study found that staff reframe restrictive practise as acts of compassion and necessary means of managing risk, thereby reducing feelings of unease derived from constantly acting against the will and wishes of their patients ( 93 ).…”
Section: The Potential For Abuse Of Power—staff Attitudes and Accountabilitymentioning
confidence: 99%
“…It's defined what we have to do and not talked about what makes it troublesome to achieve it. If goals are not met, there is no support, there is more pressure” ( 93 ).…”
Section: Reducing Coercion and Restrictive Practisesmentioning
confidence: 99%
See 3 more Smart Citations